015. A Gastrointestinal Infantile Hemangioma: A Rare Case Report and Literature Review - Kusuma, Faizurrahman Andi; Raharjo, Rudiyuwono (JBN (Jurnal Bedah Nasional), 2024)
Background : Small intestinal hemangioma in children is a rare case. The most common predilection is jejunum area. History taking, physical examination, and supporting examinations are needed to help establish the diagnosis. Case : 1 year old girl came with complaints of vomiting with blood since the age of 6 months with frequency 10x/day everytime she eats and drinks. The patient has been given treatment according to the diagnosis of pulmonary tuberculosis and digestive problem, then referred to dr. Kariadi hospital because there was no improvement. Based on examinations, the patient was diagnosed with obstructive ileus at the level of jejunum and exploratory laparotomy was performed. Multiple hemangiomas of 14 x 5 cm were found in the jejunum and confirmed by anatomic pathological examination. Six days after the operation, the child was allowed to go home.   Conclusion: Although this case is a rare case in children and include benign tumors, it is necessary to perform a quick diagnosis and appropriate management to prevent mortality and morbidity in children due to gastrointestinal bleeding.